Supporting Effective Regulation and Supervision of Index-Insurance in Francophone Africa - Assah, Fatou C.; Sberro-Kessler, Rachel (World Bank, Washington, DC, 2017)
The development of sustainable index-insurance markets requires enabling legal and regulatory environments. In addition to this regional regulatory change, the global index-insurance facility (GIIF) has supported national insurance supervision agencies with this transition. In particular, GIIF has assisted the Senegalese Insurance Supervision Agency with the development of supervisory and customer protection tools for index-insurance. This regulatory change has allowed the development of index-insurance pilots in Benin, Burkina Faso, Mali, and Senegal. Today, the CIMA region has a population of more than 145 million people, 58 percent of them living under 2 million dollars a day and most of them depending on agriculture for their livelihoods (contributing to an average of 30 percent of gross domestic product (GDP).